Organizational Effectiveness of Liaison Agencies in Coordination and Facilitation of Provincial Governments in Indonesia - Sawun, Sawun (Budapest International Research and Critics University, 2021)
This study aims to identify, analyze, and explain organizational effectiveness, inhibiting factors, and find a model of organizational effectiveness of the liaison agency in the coordination and facilitation of provincial governments in Indonesia. The method in this study is a qualitative research method with secondary and primary data sources. Primary data sources are obtained from informants using data collection techniques such as library research techniques, interview techniques, and observation. The results showed that of the seven aspects of organizational effectiveness, namely in the clarity of the objectives, the direction was noticeable but not optimal when viewed from the organizing function, in the clarity of the strategy, the liaison agency had carried out its duties as ambassadors and facilitators following the juklak (implementing instructions) and technical guidelines that apply in accordance with their respective regional regulations, in the formulation of policies it has been programmed and planned, but it requires support from various policy factors (policy actors), both actors from the government (President, ministers, commander of the TNI and others) , as well as from non-government groups (businessmen, mass media, NGOs and others), in preparing program plans and budgets to achieve strategic targets for the implementation of their duties and functions, but the implementation process has not been able to run optimally, in formulating and implementing programs for optimize pela It's just that it needs to be considered if in program implementation there must be the provision of what technical and operational support is needed, then clearly appoint the person in charge of the program and monitoring program implementation so that the program can run smoothly, in monitoring and controlling the Organization of the Liaison Body in Coordination and the facilitation of the provincial government in Indonesia is good.